Finite element analysis of hyperelastic material model for non-pneumatic tire - Ravivat Rugsaj (2019)
© 2018 Trans Tech Publications, Switzerland. This research aimed to find an appropriated hyperelastic material model for the finite element analysis (FEA) of a non-pneumatic tire (NPT). The innovative method involving water jet cutting technique was performed to prepare the tensile and compressive test specimens from the non-pneumatic tire, TWEEL, which was developed by Michelin. The stress-strain relationship of material testing results was fitted to select the suitable constitutive model. The FEA was performed and compared to the physical experiment to validate the hyperelastic material model. The suitable hyperelastic material model can be used in the development of NPT for the further work.